Clinical study of cases of intrauterine foetal death in a tertiary centre - Bhatia, Tulsi; Narshetty, Jayshree G.; Bagade, Priya; Kulkarni, Amit; Rai, Mandavi (International Journal of Research in Medical Sciences, 2016)
Background: Foetal death at any stage of pregnancy is a tragic event and one of the unhappy events in the field of obstetrics. The present study was done to determine the probable etiology for antepartum and intrapartum foetal deaths and to study the role of antenatal care in prevention of intrauterine foetal deaths. Methods: The cases of intrauterine foetal deaths in OBGY department at MGM hospital, Kalamboli and Kamothe with either ultrasound reports proving Intrauterine foetal death (IUFD) or diagnosed on clinical examination by absence of foetal heart rate with gestational age more than 28 weeks by dating from Naegle’s rule or by ultrasonography were studied. Inclusion criteria includes as following; 1) All cases of IUFD >28 weeks of gestation; 2) Baby weight of 1000 grams or more and exclusion criteria includes molar pregnancy. Results: The foetal death rate was 27.76/1000 births. Major causes of IUFD were PE and eclampsia (34.78%), unexplained (14.49%) and abruptio placentae (7.25%). Majority of the stillbirth were seen in preterm pregnancy between 34 - 36 (18.85%) weeks followed by 28 - 30 weeks (17.39%). Majority of foetuses were preterm and of birth weight between 1 - 1.5 kg (28.26%) followed by 1.5 - 2 kg (26.09%). Conclusions: Present studies showed that majority of IUFDs were preventable. Pre-eclampsia and abruption which are the major causes of IUFD can be reduced by improving education of the patient to avail obstetric care, more frequent visits for high risk pregnancies, timely reference to specialist. Early registration is an important pre-requisite for early detection of risk factors.